2018
DOI: 10.3389/fgene.2018.00365
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiling of mRNA and lncRNA Related to Tail Adipose Tissues of Sheep

Abstract: The Lanzhou Fat-Tail sheep (LFTS, long fat-tailed sheep) is an endangered sheep breed in China with a fat tail compared to the traditional local varieties, Small Tail Han sheep (STHS, thin-tailed sheep) with a small tail, and Tibetan sheep (TS, short thin-tailed sheep) with a little tail. However, little is known regarding how tail fat deposition is regulated by long noncoding RNA (lncRNA). To evaluate the lncRNA and mRNA associated with tail fat deposition and development among these breeds, high-throughput R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 48 publications
3
42
1
Order By: Relevance
“…Li and co-workers reported 5,395 DEGs between tail fat tissues of Guangling large-tailed and small-tailed Han sheep [27]. In addition, 646 DEGs between Kazak and Tibetan sheep were reported by Wang et al [26], 390 DEGs between Lanzhou Fat-Tailed and Tibetan sheep by Ma et al [29] and 602 DEGs between Small-Tailed Han and Dorset sheep by Miao et al [28]. The numbers of total genes and DEGs identi ed in the current study were signi cantly higher than previously reported gures, which may be attributable to the higher suitability of our animal models.…”
Section: Detection Of Variants In Candidate Genes Related To Tail-fatmentioning
confidence: 99%
See 1 more Smart Citation
“…Li and co-workers reported 5,395 DEGs between tail fat tissues of Guangling large-tailed and small-tailed Han sheep [27]. In addition, 646 DEGs between Kazak and Tibetan sheep were reported by Wang et al [26], 390 DEGs between Lanzhou Fat-Tailed and Tibetan sheep by Ma et al [29] and 602 DEGs between Small-Tailed Han and Dorset sheep by Miao et al [28]. The numbers of total genes and DEGs identi ed in the current study were signi cantly higher than previously reported gures, which may be attributable to the higher suitability of our animal models.…”
Section: Detection Of Variants In Candidate Genes Related To Tail-fatmentioning
confidence: 99%
“…RNA-Seq analysis by Ma and colleagues to investigate the tail fat transcriptome of Lanzhou Fat-Tailed (long fat-tailed), Small-Tailed Han (short fat-tailed), and Tibetan (short thin-tailed) sheep identi ed several differentially expressed genes (DEGs) and long non-coding RNAs (lncRNAs). GO and pathway analysis of DEGs and target genes of differentially expressed lncRNAs revealed that the majority were enriched in fatty acid metabolism and fatty acid elongation-related pathways that contribute to fat deposition [29]. Previous studies clearly indicate that the tail fat deposition ability of sheep with different tail types is a complex quantitative trait regulated by multiple genes.…”
Section: Introductionmentioning
confidence: 97%
“…Lots of studies have been explored in the research on lncRNA in male reproduction, female reproduction and growth development of sheep, including testis [27], ovary [28], uterus [29], skeletal muscle [28] and adipose tissues [30]. For the functional research of pituitary in sheep reproduction, there were 235 DE lncRNAs have been identified in embryonic and adult female sheep pituitary.…”
Section: Of 17mentioning
confidence: 99%
“…Recently, Ma et al (2018) have reported transcriptome profiling of mRNA and lncRNA related to tail adipose tissues in Lanzhou Fat-Tail sheep (long fat-tail), Small Tail Han sheep (thin-tail), and Tibetan sheep (short thin-tail; Ma et al, 2018). Differentially expressed mRNAs and lncRNAs were enriched in fatty acid metabolism and fatty acid elongation-related pathways that contribute to fat deposition.…”
Section: Sheepmentioning
confidence: 99%